Early reading at first grade predicts adult reading at age 42 in typical and dyslexic readers - Emilio Ferrer; Bennett A. Shaywitz; John M. Holahan; Sally E. Shaywitz (npj Science of Learning, 2023)
Abstract Research indicates that the achievement gap in reading between typical and dyslexic readers is already evident in first grade and persists through adolescence. However, it is not known whether this reading gap persists into adult life. In this report we use an epidemiologic sample of 312 children (typical readers = 246; dyslexic readers = 66), followed longitudinally from age 5 through adulthood and examine two fundamental questions: 1) Is reading level in 1st grade predictive of reading proficiency in adulthood in typical and dyslexic readers? and 2) Are the trajectories of reading development from 1st through 5th grade predictive of reading proficiency in adulthood in typical and dyslexic readers? Our findings indicate that early reading levels in 1st grade as well as the trajectory of reading development through the first five years of school were associated with reading scores in adulthood. This association was stronger for dyslexic than for typical readers, especially the latter factor. These findings indicate that the achievement gap between typical and dyslexic readers persists far beyond adolescence, in fact, into adult life.